RESEARCH ETHICS: A NEW PARADIGM (CAHIERS MAGELLANES-NS, 2024)
Research ethics involves the application of fundamental ethical principles to research activities which include the design and implementation of research, respect towards society and others, the use of resources and research outputs, scientific misconduct, and the regulation of research. Research ethics provides guidelines for the responsible conduct of research. In addition, it educates and monitors scientists conducting research to ensure a high ethical standard. Research ethics are expansive, from generating to using and applying knowledge. Researchers are ethically obligated to design protection strategies so that all populations, regardless of literacy level or physical or cognitive capacity, can engage in the research process in a fully informed and ethical way. If written consent is necessary, it must contain critical elements describing study procedures, voluntary capacity, risk-to-benefit ratio, and confidentiality procedures. A current, dated, and stamped consent precedes the enrollment or recruitment of study participants. The process of obtaining consent is an essential aspect of bounding one's study and ensuring ethical research behavior on the part of the researcher. (Elizabeth, 2016). It is of utmost importance for a research scholar that he/she should try to ensure the core issues of research. Deviation from the core issues can create dilemmas and risks. To avoid an unwanted situation and risk it is mandatory for a research scholar that he/she should distinguish research ethics from risk management.